2010
DOI: 10.1124/dmd.110.035014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Typical Inducers on Olfactory Xenobiotic-Metabolizing Enzyme, Transporter, and Transcription Factor Expression in Rats

Abstract: ABSTRACT:Several xenobiotic-metabolizing enzymes (XMEs) have been identified in the olfactory mucosa (OM) of mammals. However, the molecular mechanisms underlying the regulation of these enzymes have been little explored. In particular, information on the expression of the transcriptional factors in this tissue is quite limited. The aim of the present study was to examine the impact of five typical inducers, Aroclor 1254, 3-methylcholanthrene, dexamethasone, phenobarbital, and ethoxyquin, on the activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
4
24
0
1
Order By: Relevance
“…Recent studies have detected the presence of mRNA of MRP1, MRP3, MRP4, and MRP5 in adult rat OE [14], [19], [20], [33], but no data are avaible for the OE of mouse or newborn rodents. Our RT-PCR results show that both Pgp encoding genes mdr1a and mdr1b as well MRP1 are expressed in OE of newborn and adult animals of both species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have detected the presence of mRNA of MRP1, MRP3, MRP4, and MRP5 in adult rat OE [14], [19], [20], [33], but no data are avaible for the OE of mouse or newborn rodents. Our RT-PCR results show that both Pgp encoding genes mdr1a and mdr1b as well MRP1 are expressed in OE of newborn and adult animals of both species.…”
Section: Discussionmentioning
confidence: 99%
“…Also a very robust immunolocalization of MRP1 to sustentacular cells of the rat OE has recently been shown by Kudo et al [19]. Further expression of MRP1, MRP3, MRP 4 and MRP 5 has been reported in the olfactory epithelium of rat [14], [19], [20]. The few functional MDR activity tests in OE of mammals have focused on Pgp transport activity across excised olfactory tissue or whole animals, and so far no functional test for MRP1 has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the MOE serves as an epithelial surface barrier, preventing or minimizing inhaled xenobiotics, such as air pollutants and infectious agents, from entering the brain, where they can create inflammation and neurodegeneration (Prediger et al, 2006; Imamura and Hasegawa-Ishii, 2016). Third, the MOE serves as a primary site for metabolizing and removing xenobiotics in the upper respiratory tract (Chen et al, 1992; Thornton-Manning et al, 1997; Thiebaud et al, 2010). The MOE is susceptible to xenobiotic insults owing to its large surface area and direct contact with inhaled chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Transporter-mediated drug uptake involves a balance between efflux transporters such as MRPs 1, 3, 4 and 5; Pgp, and Bcrp, as well as influx transporters such as ENT1 and 2; many of these transporters have been localized in the rat OE (Genter et al, 2010; Kudo et al, 2010; Thiebaud et al, 2010; Agarwal et al, 2013). Studies have shown gemcitabine transport is mediated by hENT1, and rat ENT1 mediates gemcitabine translocation across the BBB (Thomas et al, 2008; Farrell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%